Beliefs, barriers, and promotion practices of Indian nurses’ regarding healthy eating for cancer survivors in a tertiary care hospital—A cross sectional survey - Hritika D. Pai; Stephen Rajan Samuel; K. Vijaya Kumar; Charu Eapen; Alicia Olsen; Justin W.L. Keogh (PeerJ, 2024)
Purpose To describe the beliefs, barriers and promotion practices of Indian nurses’ regarding healthy eating (HE) behaviours amongst cancer survivors, and to gain insights into whether their educational qualifications might affect the promotion of HE. Methods Data was gathered using a validated questionnaire, 388 of the approached 400 nurses who worked at a tertiary care hospital in India gave informed consent to participate in the study. The Mann-Whitney U test and the Chi square analysis (for continuous and categorical variables respectively) were performed to carry out sub-group comparisons based on the qualification of the nurses i.e., Bachelor of Science in Nursing (BSc) and General Nursing and Midwifery (GNM). Results The nurses believed that dieticians/nutritionists were primarily responsible for educating the cancer survivors regarding HE. HE was promoted by nurses’ relatively equally across multiple treatment stages (“during” treatment 24.4%, “post” treatment 23.1%; and “pre” treatment 22.3%). Nurses’ believed HE practices had numerous benefits, with improved health-related quality of life (HRQoL) (75.7%), and mental health (73.9%) being the most frequent responses. The most frequently cited barriers by the nurses in promoting HE were lack of time (22.2%), and lack of adequate support structure (19.9%). Sub-group comparisons generally revealed no significant difference between the BSc and GNM nurses in their perceptions regarding HE promotion to cancer survivors. Exceptions were how the GNM group had significantly greater beliefs regarding whether HE can “reduce risk of cancer occurrence” (p = 0.004) and “whether or not I promote HE is entirely up to me” (p = 0.002). Conclusion The nurses in India believe in the promotion of HE practices among cancer survivors across various stages of cancer treatments. However, they do face a range of barriers in their attempt to promote HE. Overcoming these barriers might facilitate effective promotion of HE among cancer survivors and help improve survivorship outcomes. Implications for cancer survivors Indian nurses employed in the two tertiary care hospitals wish to promote HE among cancer survivors, but require further knowledge and support services for more effective promotion of HE.